Potential of methane and carbon dioxide in vitro production by urochloa hybrid subjected to periods of coexistence with weeds - Meurer, Edenilson; de BRITO, Sara Carvalho; de MARCHI, Sidnei Roberto; Pinheiro, Guilherme Henrique Rodrigues; Martins, Dagoberto [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
The increased world population has raised the demand for animal proteins, forcing livestock to become productive, efficient, and environmentally sustainable. This study aimed to assess the effect of weed coexistence on productivity, nutritional quality, and potential production of greenhouse gases (GHG) by Convert HD364 grass (Urochloa hibrida cv. Mulato II) under pasture renovation conditions. The experiment was carried out in a randomized block design with four replications and treatments consisting of eight coexistence periods: 0, 15, 30, 45, 60, 75, 90, and 120 days after seedling emergence. Phytosociological assessments were performed in the weed community at the end of each coexistence period. The Convert HD364 grass was assessed for the morphological and chemical-bromatological parameters and for the GHG emission potential. Productivity, nutritional quality, and energy value of the Convert HD364 grass decreased proportionally with the increased period of weed coexistence. The non-coexistence with weeds results in a better in vitro digestibility of organic matter and, consequently, decreases the potential of GHG emission by the dry matter of the Convert HD364 grass.
Potencial de produção in vitro de metano e dióxido de carbono pela urochloa híbrida submetida a períodos de convivência com plantas daninhas
Keywords: Digestibility; Energy value; Morphometry; Mulato II; Nutritional quality; Productivity; Urochloa hibrida cv